Feeding habits of Carabidae (Coleoptera) associated with herbaceous plants and the phenology of coloured cotton - Danilo Henrique da Matta; Francisco Jorge Cividanes; Robson José da Silva; Mariana Nardin Batista; Alessandra Karina Otuka; Ezequias Teófilo Correia; Sidnéia Terezinha Soares de Matos (Acta Scientiarum. Agronomy, 2017)
The carabids (Coleoptera: Carabidae) are recognized as polyphagous predators and important natural enemies of insect pests. However, little is known about the feeding habits of these beetles. In this work, we determine the types of food content in the digestive tracts of nine species of Carabidae associated with herbaceous plants and different growth stages of coloured cotton. The food contents were evaluated for beetles associated with the coloured cotton cv. BRS verde, Gossypium hirsutum L. latifolium Hutch., adjacent to weed plants and the flowering herbaceous plants (FHPs) Lobularia maritima (L.), Tagetes erecta L., and Fagopyrum esculentum Moench. The digestive tract analysis indicated various types of diets and related arthropods for Abaris basistriata, Galerita brasiliensis, Scarites sp., Selenophorus alternans, Selenophorus discopunctatus and Tetracha brasiliensis. The carabids were considered to be polyphagous predators, feeding on different types of prey.